Developing rural communication through digital innovation for village tourism - Dewi Yanti; D. Yadi Heryadi; Juliana; Pandu Adi Cakranegara; Muhammad Kadyrov (Faculty of Communications Science, Dr. Soetomo University, 2023)
This study examines how digital information facilitates communication in the tourism industry to spur innovation in rural communities. Digital platforms have helped Pentingsari Village improve its tourism economy and document its development. This study used content analysis on social media and online reviews to examine Pentingsari Village's change from the New Regime era to the present day. Our research reveals minor alterations in popular perceptions towards village tourism and its effects on local culture and land ownership - effective use of Internet platforms has changed negative perceptions about the tourism industry's exploitation of indigenous land and culture. This approach is viewed as an innovative means of achieving sustainable development while preserving the cultural heritage of local communities and bolstering their economies. This study is a blueprint for how other rural communities can harness similar insights to enhance their well-being. It demonstrates how rural towns can draw inspiration from Pentingsari's utilisation of digital communication to stimulate creativity, showcase their unique attractions, and monitor their progress via digital platforms, which is instrumental in attracting tourists and investors to these areas.